Jeszcze o prapolskim etnonimie Polanie - Łuczyński, Michał (Slavia Occidentalis, 2016)
The purpose of the article is to review the question of the use of the Proto-Polish ethnonym Polanie. According to the opinion traditionally adopted in historiography, this name referred to one of the tribes inhabiting Greater Poland (the territories of Kuyavia) whose territorial conquests led to the establishment of the Polish State. On the basis of a semantic analysis of the earliest written occurrences of this name, the author develops the thesis that it originally designated a tribe residing in the western part of Lesser Poland, and only at the beginning of the 11th century, again, it came to denote the ‘inhabitants of Poland’ (understood as the state of Bolesław I the Brave).